Inclusive employment: barriers and ways to overcome them - Saule Okutayeva; Zubirash Smagulova; Ardak Mukanova; Emin Askerov; Oleg Metsik (Entrepreneurship and Sustainability Issues, 2024)
Inclusive employment is a comprehensive system of measures to ensure equal access to employment for all social groups, including persons with disabilities. Inclusive employment involves developing and implementing policies and practices aimed at creating accessible and supportive work environments, adapting workplaces and providing the necessary resources and training to facilitate the inclusion of workers with disabilities in the workplace. This study aims to conduct a comprehensive analysis of the state of the inclusive labour market and identify the key barriers faced by persons with disabilities in the employment process. Particular attention is paid to employers' perceptions of the problem and the identification of factors that require priority attention from government and business. To achieve this goal, the study used methods of expert survey of employers, as well as the method of in-depth interviews with persons with disabilities. The article focuses on the problems faced by people with disabilities when looking for a job and employers' attitudes towards hiring such employees. The research involved expert interviews with representatives of various companies and in-depth interviews with persons with disabilities. The results of the study show that the main barriers to employment are discriminatory attitudes of employers, lack of information about the opportunities and rights of persons with disabilities, and problems with workplace adaptation. The authors offer a number of recommendations to improve the situation, including developing support and training programmes and information campaigns for employers.